Socioeconomic Determinants of Employment and Further Study Status of University Graduates: Evidence From a Higher Educational Institute of Nepal (Quest Journal of Management and Social Sciences, 2021)
Background: There has been a tremendous expansion of higher education in Nepal over the years and this expansion has increased the number of graduates entering the job markets. Objective: Within this context, the objective of this paper is to find socioeconomic determinants of employment and opportunities for further studies on the status of management graduates of Pokhara University, a relatively young university in Nepal.Method: The survey instrument was adapted using the questionnaire developed by the University Grants Commission of Nepal. The primary data was collected from 261 graduates, who were graduated in 2017 and 2018, from the School of Business, Pokhara University. The determinants of being employed and pursuing higher study were carried out using logistic regression analysis.Result: Of the total 261 respondents, the study had a well-balanced gender distribution with females making up 51%, a majority (58%) of respondents were from Bachelor level, and Brahmin comprised around half. Most of the graduates (87%) are being involved either in a job or pursuing further studies. Nearly one-third (31%) of the graduates were pursuing further studies. The logistic regression analysis revealed that gender and graduation level are significant predictors of employment and pursuing further study. Male graduates are more likely to be employed compared to female graduates (Adjusted Odds Ratio=1.44). In contrast, concerning pursuing further study, being females, they are 56% more likely to pursue their further study compared to male graduates (Adjusted Odds Ratio=1.56).Conclusion: The status of management graduates is very good as most of the graduates (87%) are already employed or pursuing further studies. However, male graduates have better job opportunities than female graduates and this indicates the socio-economic status such as gender discrimination that reflects the national scenario.